PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN KOMPETENSI PEDAGOGIK GURU TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI SE-CABANG DINAS PENDIDIKAN WILAYAH IX - Sakto Frans Situmorang; Robert Juni Tua Sitio; Bernard Bistok Lubis; Binur Panjaitan; Junjungan Simorangkir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine and analyze the positive and significant influence of principals’ managerial abilities and teachers’ pedagogical competence on students’ learning achievement in public senior high schools under the Regional Education Office Branch IX of North Sumatra. The research employed a descriptive quantitative method. The population consisted of 490 students from SMA Negeri 1 Pakkat, SMA Negeri 1 Parlilitan, and SMA Negeri 1 Tarabintang, with a sample of 74 students or 15% of the population. Instrument testing was conducted on 30 students outside the research sample, and all research instruments were declared valid and reliable. Data were collected through a closed-ended questionnaire consisting of 45 items. The results showed that principals’ managerial abilities had a positive and significant effect on students’ learning achievement, with an Fcount value of 30.868 > Ftable 3.15 and a contribution of 30%. Teachers’ pedagogical competence also had a positive and significant effect on students’ learning achievement, with an Fcount value of 46.118 > Ftable 3.15 and a contribution of 39%. Simultaneously, principals’ managerial abilities and teachers’ pedagogical competence had a positive and significant effect on students’ learning achievement, with an Fcount value of 27.831 > Ftable 3.15 and a contribution of 43.9%. Therefore, the research hypothesis was accepted and H0 was rejected.